Advancements in performance monitoring: A systematic review of sensor technologies in rowing and canoeing biomechanics - Cruz, M. I.; Sarmento, H.; Amaro, A. M.; Roseiro, L.; Gomes, B. B. (Sports, 2024)
A comprehensive understanding of sports biomechanics is essential for optimizing athletic performance. Recent advancements in sensor technology, particularly inertial sensors, have transformed the landscape of sports performance analysis. These sensors offer profound insights into the kinematic and kinetic aspects of sports, with a particular impact on water-based sports such as rowing and canoeing. This systematic review aims to establish a comprehensive framework for examining sensor technologies and evaluating biomechanical performance in rowing and canoeing. The authors systematically searched four prominent databases (Web of Science, Scopus, Science Direct, and Sage Journals), concentrating on research that has employed sensors to analyze critical performance variables in rowing and canoeing. Our exclusion criteria included manuscripts that exclusively addressed ergometer-based studies, those lacking sensor-related content, unrelated subjects, and publications dating back more than 15 years. The authors used the National Heart, Lung, and Blood Institute Quality Assessment Tools to assess study quality and bias risk. A total of 11 studies were included in this review. This review also acknowledges the limitations, such as the exclusion of gray literature and studies in languages other than English, which may have limited the scope of the research. The studies were synthesized qualitatively, focusing on key variables, including oar/paddle force, boat speed, and technique, and were analyzed, providing quantitative insights. Sensor technology has ushered in a new era of rowing and canoeing performance analysis.